HUBUNGAN KEMAMPUAN KOMUNIKASI INTERPERSONAL GURU DENGAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN FIKIH DI MIN KABUPATEN SLEMAN (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2016)
This study aims to determine the relationship between interpersonal communication abilities of teachers and learning achievement students. The study used quantitative research methods conducted in MIN Sleman. The population in this study were students MIN Sleman district in academic year 2013/2014. The sampling technique used was 100 students. The technique of collecting data using questionnaires and documentation. Methods of data analysis using statistical analysis of the correlation of product moment. The results of this study shows that the achievement of jurisprudence students study subjects MIN Sleman has an average of 81.12. and there are three students who score below 75. The results of this study also indicate that learning achievement subjects of jurisprudence influenced by interpersonal communication skills of teachers. The relationship between the two variables is positive means of mutual support. The higher the interpersonal communication skills of teachers, the higher learning achievement in the subjects of jurisprudence and vice versa if the interpersonal communication skills of teachers lower the learning achievement of jurisprudence subjects will also be lower.